COLLABORATIVE TRIAL AND QUALITY CONTROL IN CHEMICAL ANALYSIS - Narsito Narsito (Universitas Gadjah Mada, 2002)
This paper deals with some practical problems related to the quality of analytical chemical data usually met in practice. Special attention is given to the topic of quality control in analytical chemistry, since analytical data is one of the primary information from which some important scientifically based decision are to be made. The present paper starts with brief description on some fundamental aspects associated with quality of analytical data, such as sources of variation of analytical data, criteria for quality of analytical method, quality assurance in chemical analysis. The assessment of quality parameter for analytical method like the use of standard materials as well as standard methods is given. Concerning with the quality control of analytical data, the use of several techniques, such as control samples and control charts, in monitoring analytical data in quality control program are described qualitatively. In the final part of this paper, some important remarks for the preparation of collaborative trials, including the evaluation of accuracy and reproducibility of analytical method are also given.